2017
DOI: 10.2147/ndt.s145069
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate prevents rats from the clozapine-induced hepatic steatosis and elevation in plasma triglycerides

Abstract: Clozapine is an atypical antipsychotic with therapeutic efficacy in treatment-resistant schizophrenia patients and low incidence of extrapyramidal side effects. However, the use of clozapine has been limited by its adverse effects on metabolism. Artesunate is a semisynthetic derivative of artemisinin and was shown to decrease the plasma cholesterol and triglyceride in rabbits and rats in recent studies. The aim of this study was to examine possible effects of artesunate on the clozapine-induced metabolic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…These findings were confirmed in our in vivo study, where clozapine was shown to induce rat liver steatosis (Zlatković et al 2014 ). Liver steatosis, as well as an increase in plasma triglycerides and FFAs, due to clozapine treatment, was confirmed by later studies (Li et al 2017 ; Liu et al 2017 ). Moreover, a single intraperitoneal injection of clozapine (50 mg/kg) was demonstrated to down-regulate genes involved in FFA β-oxidation and lipolysis, leading to lipid accumulation in rat liver (Fernø et al 2009 ) (Fig.…”
Section: Major Pathophysiological Pathways In Dilimentioning
confidence: 61%
“…These findings were confirmed in our in vivo study, where clozapine was shown to induce rat liver steatosis (Zlatković et al 2014 ). Liver steatosis, as well as an increase in plasma triglycerides and FFAs, due to clozapine treatment, was confirmed by later studies (Li et al 2017 ; Liu et al 2017 ). Moreover, a single intraperitoneal injection of clozapine (50 mg/kg) was demonstrated to down-regulate genes involved in FFA β-oxidation and lipolysis, leading to lipid accumulation in rat liver (Fernø et al 2009 ) (Fig.…”
Section: Major Pathophysiological Pathways In Dilimentioning
confidence: 61%
“…In a more recent study, olanzapine-administered (for 2 weeks) rats showed severe liver damage indicated by loss of normal architecture, vacuolar degeneration of hepatocytes and fatty changes in the liver 100. In a study from our group, daily intraperitoneal injection of clozapine for 6 weeks significantly increased plasma levels of triglycerides, led to hepatic steatosis and fibrosis along with increased activities of alanine aminotransferase and aspartate aminotransferase in male Wistar rats, but showed no effects on blood glucose, insulin levels, and total cholesterol 101…”
Section: Metabolic Effects and Nafld Of Aaps In Animal Studiesmentioning
confidence: 70%
“…Hematological abnormalities and anemia of diverse etiology are frequently associated with chronic liver diseases [ 26 , 27 ]. In rats, clozapine induces hepatic oxidative stress leading to liver injury [ 28 ] and hepatic steatosis with elevated triglyceride levels [ 29 ]. In our study, MCV, measuring the average volume of red blood cells, is unchanged in the medicated groups compared to controls (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to haloperidol, which seems to show only rare hematological effects, it is known that clozapine induces dyscrasias of leukocytes [ 58 ] and erythrocytes [ 7 ] in humans, and chronic liver injury in mice [ 59 ] and rats [ 28 , 29 ]. There is growing evidence that clozapine medication is associated with severe drug-induced hepatic injury in patients [ 60 ].…”
Section: Discussionmentioning
confidence: 99%